Chronic Lipoid Pneumonia in a 9-Year-Old Child Revealed by Recurrent Chest Pain - A. Hochart; C. Thumerelle; L. Petyt; C. Mordacq; A. Deschildre (Case Reports in Pediatrics)
Lipoid pneumonia in children is a rare disorder due to accumulation of fatty oily material in the alveoli and usually associated with an underlying condition. In absence of obvious context, diagnosis remains difficult with nonspecific clinical and radiological features. We report the first case of voluntary chronic aspiration of olive oil responsible for exogenous lipoid pneumonia, in a previously healthy 9-year-old boy. Clinical presentation was atypical; LP was revealed by isolated chest pain. We discuss radiological and bronchial alveolar lavage characteristics suggestive of lipoid pneumonia. Conclusion. Lipoid pneumonia is a disease to be reminded of in children, which can occur with original findings in terms of etiology and clinical presentation.